In Vitro Evaluation of the Combinatorial Effect of Naringenin and Miltefosine against Leishmania amazonensis - Vinícius Lopes Lessa; Gustavo Gonçalves; Beatriz Santos; Victoria Cruz Cavalari; Rafael Felipe da Costa Vieira; Fabiano Borges Figueiredo (MDPI AG, 2024)
Leishmania amazonensis causes a clinical form called diffuse cutaneous leishmaniasis (DCL) with challenges to treatment, like low efficiency and drug toxicity. Therefore, it is necessary to investigate new therapies using less toxic leishmanicidal compounds, such as flavonoids like naringenin, and their combination with conventional drugs, such as miltefosine. Antileishmanial dose/response activity, isobologram, calculation of dose reduction index (DRI), and fractional inhibitory concentration index (FICI) tests were performed on in vitro assays using reference promastigote forms of L. amazonensis (IFLA/BR/67/PH8) to assess the combinatorial effect between naringenin and miltefosine. The in vitro results of isobologram, DRI, and FICI calculations showed that the combination of the compounds had an additive effect and was able to reduce the half maximal inhibitory concentration (IC50) of miltefosine in the promastigote forms of the parasite compared to the treatment of the drug alone. This study demonstrated in vitro the viability of a combination action of the flavonoid with the treatment with miltefosine, opening space for further investigations on the association of natural compounds with the drugs used for the treatment of L. amazonensis.